CO2 supply is a powerful tool to control homoacetogenesis, chain elongation and solventogenesis in ethanol and carboxylate fed reactor microbiomes - de Leeuw, Kasper D.; van Willigen, Marius J. W.; Vrauwdeunt, Ton; Strik, David P. P. T. B. (Frontiers in Bioengineering and Biotechnology, 2024)
Anaerobic fermentation technology enables the production of medium chain carboxylates and alcohols through microbial chain elongation. This involves steering reactor microbiomes to yield desired products, with CO2 supply playing a crucial role in controlling ethanol-based chain elongation and facilitating various bioprocesses simultaneously. In the absence of CO2 supply (Phase I), chain elongation predominantly led to n-caproate with a high selectivity of 96 Cmol%, albeit leaving approximately 80% of ethanol unconverted. During this phase, C. kluyveri and Proteiniphilum-related species dominated the reactors. In Phase II, with low CO2 input (2.0 NmL L-1 min-1), formation of n-butyrate, butanol, and hexanol was stimulated. Increasing CO2 doses in Phase III (6 NmL L-1 min-1) led to CO2 utilization via homoacetogenesis, coinciding with the enrichment of Clostridium luticellarii, a bacterium that can use CO2 as an electron acceptor. Lowering CO2 dose to 0.5 NmL L-1 min-1 led to a shift in microbiome composition, diminishing the dominance of C. luticellarii while increasing C. kluyveri abundance. Additionally, other Clostridia, Proteiniphilum, and Lactobacillus sakei-related species became prevalent. This decrease in CO2 load from 6 to 0.5 NmL L-1 min-1 minimized excessive ethanol oxidation from 30-50% to 0-3%, restoring a microbiome favoring net n-butyrate consumption and n-caproate production. The decreased ethanol oxidation coincided with the resurgence of hydrogen formation at partial pressures above 1%. High concentrations of butyrate, caproate, and ethanol in the reactor, along with low acetate concentration, promoted the formation of butanol and hexanol. It is evident that CO2 supply is indispensable for controlling chain elongation in an open culture and it can be harnessed to stimulate higher alcohol formation or induce CO2 utilization as an electron acceptor.